2018
DOI: 10.1177/2047487318818265
|View full text |Cite
|
Sign up to set email alerts
|

Parity and risk of maternal cardiovascular disease: A dose–response meta-analysis of cohort studies

Abstract: Background Parity has been reported to play an important role in the development of cardiovascular disease; however, the results are still controversial. We aimed to conduct a meta-analysis of cohort studies to assess quantitatively the association between parity and cardiovascular disease risk. Methods PubMed and Web of Science databases were searched to 1 June 2018, supplemented by manual searches of the bibliographies of retrieved articles. And multivariate-adjusted relative risks were pooled by using rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 45 publications
9
70
0
Order By: Relevance
“…The ndings of the current study about the association of parity number with incident CVD among women are consistent with a meta-analysis study on this issue by Li et al [9]. in which they found a non-linear Jshaped dose-response relationship between the number of parity and CVD among women.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The ndings of the current study about the association of parity number with incident CVD among women are consistent with a meta-analysis study on this issue by Li et al [9]. in which they found a non-linear Jshaped dose-response relationship between the number of parity and CVD among women.…”
Section: Discussionsupporting
confidence: 92%
“…They also found that each live birth was associated with a 1% non-signi cant increased risk for CVD mortality (I 2 = 86.4%). It should be noted that the signi cant heterogeneity in these two meta-analyses [9,21] could be related to different study populations, sample sizes and other epidemiologic aspects of studies. Marginally signi cant increased CVD risk for women with ≥ 4 parity in our results agrees with the ndings of other studies [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a dose-response meta-analysis to assess quantitatively the association between parity and maternal CVD risk was conducted in the paper by Li et al 10 It consisted of 10 prospective cohort studies performed from 1987 to 2018. The investigators reported a potential non-linear J-shaped dose-response relationship between them and concluded the risk of CVD increased by 14% among parous women compared with nulliparous women, and an increasing number of parity was associated with a non-linearly increased CVD risk.…”
mentioning
confidence: 99%